1989
DOI: 10.1590/s0074-02761989000800065
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic position of the Ctenostylidae (= Lochmostyliinae; Diptera: Schizophora)

Abstract: It is shown that Ctenostylidae Bigot (1882) is a valid senior synonym of Lochmostylidae Hendel (1935). The morphology of the Ctenostylidae is considered and compared with the Pyrgotidae. It is concluded that the Ctenostylidae are not closely related to the Pyrgotidae, but form an isolated taxon of obscure relationship. Notes on a speciment of Ctenostylum sp. and a revised key to genera of Ctenostylidae are given

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…As mentioned in the Introduction, Ctenostylidae was once regarded as part of Pyrgotidae, but its phylogenetic position was unresolved in the latest systematic studies (McAlpine ; Korneyev ). Even though it has an extremely long terminal branch, both the ML and BI trees (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the Introduction, Ctenostylidae was once regarded as part of Pyrgotidae, but its phylogenetic position was unresolved in the latest systematic studies (McAlpine ; Korneyev ). Even though it has an extremely long terminal branch, both the ML and BI trees (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Han () reviewed the taxonomic history of the family Ctenostylidae as follows: Ctenostylids were once assigned to the family Pyrgotidae of the superfamily Tephritoidea (e.g. Hendel ; Keiser ; Aczél ), but McAlpine () treated them as the family Ctenostylidae and suggested that they did not even belong to the superfamily Tephritoidea based on the postabdominal structures of both sexes. Korneyev () was also unsure of the relationship between the Ctenostylidae and Tephritoidea, but he suggested that if the Ctenostylidae belongs to the superfamily Tephritoidea, then it is related to the Platystomatidae + Pyrgotidae + Tephritidae group of families.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrgotidae are closely related to the family Tephritidae (Korneyev, 1999). Existing classifi cation of the family was proposed by Aczél (1956), with further improvements proposed by McAlpine (1978McAlpine ( , 1990. Detailed comparative morphological study of pyrgotid genera worldwide showed the need of further taxonomic improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Four striking features are peculiar to Ctenostylidae: vestigial mouthparts; lack of ocelli; viviparity; and the very complex branching of the female arista (McAlpine 1990). Additionally, the ctenostylids are recognized by their light yellow color pattern (with some red or black spots), the sexually dimorphic head, the subequal size of the head and thorax, their long slender legs and patterned wings (Korneyev 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Ctenostylidae were classified near the Oestridae (Brauer 1863), Sepsidae (Brauer 1887) and Conopidae (Bigot 1882) and later tentatively placed as subfamily Lochmostyliinae in Pyrgotidae Hennig 1952;Aczél 1956b;Steyskal 1967). McAlpine (1990), through comparative morphological analysis, listed the ctenostylids within Tephritoidea until they could be shown either to have a particular relationship to another Schizophora taxon or in its own superfamily. Posteriorly, the exclusion of Lochmostyliinae from Pyrgotidae was accepted by Barraclough (1994Barraclough ( , 1995aBarraclough ( , 1995bBarraclough ( , 1998, Korneyev (2001), Han (2006), Rafael et al (2009) and Câmara & Rafael (2013).…”
Section: Introductionmentioning
confidence: 99%